(untitled) (Eurasian Medical Research Periodical, 2024)
In the traditional treatment of external abdominal hernias in women of fertile age in the early postoperative period, the frequency of surgical complications was 13.4%; in the long-term period, 8.5% of patients had a recurrence of the hernia. A critical analysis revealed that the unsatisfactory results were due to the shortcomings of tactical approaches in the ability to perform alloplasty in women of reproductive age